2014
DOI: 10.1103/physrevd.90.124058
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational redshift of photons traversing a collapsing dust cloud and observable consequences

Abstract: We analyze the frequency shift of photons propagating on an asymptotically flat spacetime describing a collapsing, spherical dust cloud. We focus on the case where the interaction of the photons with the matter can be neglected. Under fairly general assumptions on the initial data characterizing the collapse, we show that photons with zero angular momentum which travel from past to future null infinity, crossing the collapsing cloud through its center, are always redshifted with respect to stationary observers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The numerical integration along the radial light rays required for this computation was performed using a fourth-order Runge-Kutta algorithm. Our numerical solutions were checked to be self-convergent to fourth order accuracy and consistent with the analytic results for the case of homogeneous density distributions [29].…”
mentioning
confidence: 68%
See 3 more Smart Citations
“…The numerical integration along the radial light rays required for this computation was performed using a fourth-order Runge-Kutta algorithm. Our numerical solutions were checked to be self-convergent to fourth order accuracy and consistent with the analytic results for the case of homogeneous density distributions [29].…”
mentioning
confidence: 68%
“…Important information regarding the nature of a collapsing object is revealed from the study of the spectrum of electromagnetic radiation emitted from the surface or the interior of the object, see for example [22][23][24][25][26][27][28]. In this work, following [29], we consider a different physical scenario in which the radiation, instead of being generated from the interior of the collapsing object is originated from a distant source and crosses the collapsing object without interacting with the matter. For instance, this radiation could be emitted from a distant supernova explosion or be part of the cosmic microwave background.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence supporting this proposal came from the analysis of radial photons from an external source passing through a collapsing spherical dust cloud. As shown in [24], the total frequency shift of such photons relative to asymptotic static emitters and observers is always toward the red. Moreover, the analysis in I revealed that the photon's energy measured by the asymptotic observer is gradually redshifted toward zero in the black hole case, whereas whenever a globally naked singularity forms the redshift of these radial photons remains finite and their frequency shift exhibits an abrupt cutoff once they have been detected by the observer who has crossed the Cauchy horizon (see Figs.…”
Section: Introductionmentioning
confidence: 86%